Islamic Educational Perspectives in the Sara Pataanguna Philosophy of the Buton Community - Djalia, La Ode Sahrin; Rahim, Abdul; Jumaydin, Jumaydin; Kartika, Nia (Al-Fikru: Jurnal Ilmiah, 2026)
This study aims to examine the Islamic educational perspective on the Sara Pataanguna philosophy of the Buton community. The discussion focuses on three aspects: the philosophical foundations of Sara Pataanguna, the concepts of Islamic education reflected in its values, and the relevance of Islamic educational concepts to the philosophy. This research employs a library research method through the examination of books, scholarly journals, and other scientific works relevant to the topic. Data were collected from various academic sources and analyzed using philological, theoretical, philosophical, and anthropological approaches. The findings reveal that Sara Pataanguna contains Islamic educational values that correspond to the fundamental dimensions of Islamic education, namely aqidah (faith), ibadah (worship), and akhlaq (morality). The philosophy emphasizes the development of human character through the cultivation of akhlaq al-karimah (noble character), reflecting educational efforts that are consistent with the objectives of Islamic moral education. Furthermore, the humanitarian values embedded in Sara Pataanguna are highly relevant to the goals of Islamic education, as they encourage self-awareness, social responsibility, mutual respect, compassion, and obedience to Allah as the foundation of harmonious human relationships.